Explaining the use of online agricultural decision support tools with weather or climate information in the Midwestern United States. (1st February 2021) - Lu, Junyu; Singh, Ajay S.; Koundinya, Vikram; Ranjan, Pranay; Haigh, Tonya; Getson, Jackie M.; Klink, Jenna; Prokopy, Linda S.
Abstract: Agricultural decision support tools (DSTs) with weather or climate information can provide useful information to help stakeholders make operational farming decisions and adapt to increasingly variable weather or climate in the context of climate change. However, many of these DSTs are still not fully utilized. Understanding the use of DSTs can help identify strategies to promote their usage to more end-users. This study surveyed farmers (n = 2, 633) and advisors (n = 2, 719) across 12 states in the Midwest to draw comparisons on their usage of DSTs and factors influencing the usage. The advisors are more likely to take advantage of free and publicly available sources than farmers. Advisors are also more likely to agree on the usefulness of DSTs, feel social pressure to use DSTs, be concerned and perceive risks from variable weather, believe in climate change, and show positive attitudes towards climate change adaptation than farmers. Concerns about weather or climate, descriptive social norms, greater farm size, and general propensity to adopt a new technology are positively associated with higher adoption rate of DSTs for both farmers and advisors. Higher level of perceived behavioral control to deal with weather-related risks, injunctive social norms, gender (male), and age are positively associated with higher adoption rate of DSTs for only advisors. Positive adaptation attitude towards climate change and higher education level are positively associated with higher adoption rate of DSTs for only farmers. Unlike advisors, age is negatively associated with higher adoption rate of DSTs for farmers. Implications of our findings include DST educators leveraging social networks and reinforcing social norms to promote usage among current non-users, building up both farmers' and advisors' confidence and knowledge in using DSTs, understanding the role of advisors as "change agents" to promote DST usage among farmers, and connecting networks of "innovators" and "early adopters." With more and more DSTs developed, future scholarship can draw upon our findings to understand how to encourage DSTs adoption among current non-users and extend to other regions. Highlights: Advisors report significant higher use of online DSTs than farmers. Concerns about weather/climate and descriptive social norms impact both farmers and advisors. Perceived behavioral control and injunctive social norms only impact advisors. Reinforcing social norms and connecting networks of early adopters can help promote DSTs. Advisors could act as "change agents" to promote DSTs usage among farmers.